2014
DOI: 10.3896/ibra.1.53.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal effects of propolis/polylactic acid (PLA) nanofibres obtained via electrospinning

Abstract: Electrospinning of propolis / polylactic acid (PLA) fibres was investigated for propolis concentrations from 0-10% (w/v). Solutions could not be spun when the amount of propolis was over 8% (w/v). Mechanical characterization indicated that propolis reduced the tensile strength. The fibre mats exhibited poorer mechanical performance when the propolis concentration was increased. At propolis concentrations of 2-6% (w/v), the fibres were smooth, bead-free and homogeneous. When the concentration of propolis was mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 24 publications
1
26
0
1
Order By: Relevance
“…[ 31,32 ] Among the biocompatible scaffold materials, polylactic acid (PLA) and PCL were widely used in tissue engineering through electrospinning or EHD jetting techniques because of their good mechanical and structural properties. [ 30,33,34 ] However, these materials present low bioactivity and hydrophobicity, which could reduce cell affinity and low tissue regeneration rates. [ 35 ] Therefore, the surface modification of electrospinning and EHD jetting scaffold has been studied by combining other biomaterials to take advantages of individual components for wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…[ 31,32 ] Among the biocompatible scaffold materials, polylactic acid (PLA) and PCL were widely used in tissue engineering through electrospinning or EHD jetting techniques because of their good mechanical and structural properties. [ 30,33,34 ] However, these materials present low bioactivity and hydrophobicity, which could reduce cell affinity and low tissue regeneration rates. [ 35 ] Therefore, the surface modification of electrospinning and EHD jetting scaffold has been studied by combining other biomaterials to take advantages of individual components for wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…Electrospinnability of propolis by help of polymer solutions has been investigated with other types of polymers in recent studies [13,14].…”
Section: Sem Micrographs Of Electrospun Samplesmentioning
confidence: 99%
“…Propolis nanofiber fiber membrane with antibacterial activity were prepared by an electrospinning technique for different application areas. Propolis extract was used as an active ingredient, and polyvinylpyrrolidone (PVP) K90, polycaprolactone (PCL), polyurethane (PU) , polyvinyl alcohol (PVA) and Polycaprolactone (PCL) were used as the polymer matrix [24][25][26][27][28][29]. The antibacterial activity could be used against Streptococcus mutans, Staphylococcus aureus (S. aureus), Staphylococcus epidermidis, Proteus mirabilis, Bacillus cereus, and Escherichia coli, as well as against gram positive bacteria (S. aureus), gram negative bacteria (A. baumannii and P. aeruginosa) [31].…”
Section: Introductionmentioning
confidence: 99%
“…Previous mechanical characterisation showed that propolis reduces the tensile strength. Fiber mats exhibit worse mechanical performance when the propolis concentration increases [27]. Propolis has an effect on the mechanical properties of the fiber mat, hence fiber mat mechanical properties are improved by adding nanocellulose and polyurethane PU [25][26].…”
Section: Introductionmentioning
confidence: 99%